Parents' Role in Developing Self-Regulation to Early Age Children - Helena, Helena; Sari, Siska Kurnia; Putra, Toni Eka (Khalaqa: Journal of Education and Learning, 2023)
Parents are the foundation stone of all children's knowledge and skills. The role of parents significantly contributes to reducing unwanted aspects related to externalizing, internalizing and hyperactivity behavior. Good parenting will also have an impact on every child's behavior. All forms of parental behavior will be recorded and imitated by children, so instead of that, parents must display positive behavior in accordance with the rules and norms of society. Through roles that are in accordance with community norms carried out by parents, good self-regulation will also be formed in children. Children who have high self-regulation can control themselves well, manage their emotions and adapt their behavior to their environment. the role of parents is to set a good example, provide a stimulus according to the child's development and the right affection bestowed on the child. The purpose of this review is to present empirical evidence about the role parents play in the development of self-regulation in children.